UPAYA MENGEMBANGKAN KREATIVITAS ANAK MELALUI KEGIATAN BERMAIN KONSTRUKTIF DENGAN MENGGUNAKAN MEDIA BALOK DI TK ALIFEA SAMARINDA - Andi - Aslindah (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2018)
This study aims to determine the development of children's creativity through constructive play activities using media blocks. Constructive play is a form of game by using physical objects to build or create things. This game occurs when children engage in a creation or construction of a product or a problem solving of their own creation. This research is a Classroom Action Research (PTK) or Classroom Action Research. This study was conducted in two cycles. Subjects in this study were group A semester II of Kindergarten Alifea academic year 2016/2017, as many as 13 children (5 women and 8 men) with the aspect that is assessed that is participation, attention, independence, creativity and ability to tell. Data creativity of children in constructive play with media beam collected by using the method of observation with the instrument in the form of observation format sheet. Research data were obtained and analyzed qualitatively. Based on the results of data analysis obtained is on the first cycle of 46.1%, Cycle II obtained data of 81.5% So there is an increase in creativity development from cycle I to cycle II of 35.4%